2011
DOI: 10.1080/15325008.2011.567220
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Reactive Power Expansion Planning

Abstract: This article presents a penalty successive linear programming approach for optimum investment of reactive power in networks. Unlike many successive linear programming algorithms, the proposed approach is based on a successive linear programming framework that admits a convergence proof for non-linearly constrained problems of general form. The penalty successive linear programming approach produces a pattern of new reactive sources that satisfy voltage profile requirements in normal and contingent states of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A wide range of conventional optimization techniques have been used to handle the reactive power optimization problem, it has been found that all of these techniques were dealing mainly with continuous variable and they were suffering from convergence toward the local optimal solutions, these methods required some mathematical assumptions such as differential convexity property of the objective function [4], [5]. As the years went by, many researchers got interested in the field of reactive power optimization and proposed various optimization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of conventional optimization techniques have been used to handle the reactive power optimization problem, it has been found that all of these techniques were dealing mainly with continuous variable and they were suffering from convergence toward the local optimal solutions, these methods required some mathematical assumptions such as differential convexity property of the objective function [4], [5]. As the years went by, many researchers got interested in the field of reactive power optimization and proposed various optimization techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The development of power electronic based FACTS devices opened up new ways of controlling the power systems. They FACT devices have the capability of controlling both in steady state and dynamic control of power system [7].FACTS devices are incorporated for improving the power transfer capability, laudability of transmission lines, voltage stability, power loss reduction, damping of power oscillations, elimination of new transmission lines construction, and reactive power management etc., widely [8][9][10][11][12][13][14][15][16][17][18]. By not delimiting the system security, the pre-fixed thermal limits are considered to load conventional transmission systems using an important tool called FACTs device [19].…”
Section: Introductionmentioning
confidence: 99%
“…A Covariance matrix based evolutionary strategy for reactive power planning as well as enhancement of voltage stability is presented in [29]. Reactive power expansion planning is presented in [30]. An idea for optimal VAR planning in distribution feeders are presented in [31] where the locations of capacitors are determined by a heuristic approach.…”
mentioning
confidence: 99%